The preventive detention. Electronic surveillance replaceable. (2015)
This research analyzes the purposes, classes, origin and requirements of the prison custody. This paper also addresses the electronic surveillance and its administrative regulation in Colombia. The possibility of replaced the custody by electronic surveil